THE ATTITUDE OF THE PEDAGOGICAL SPECIALITIES’ STUDENTS OF THE UNIVERSITY OF LATVIA TO THE STUDY COURSE OF CIVIL DEFENCE - Porozovs, Juris; Dudkina, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In Latvia the Civil Defence course is a compulsory course for all higher education study programs. The aim of the study was to find out the attitude of the students of pedagogy specialties of the University of Latvia towards the Civil Defence course, to study the students' self-assessment of understanding the most important topics of the Civil Defence course and the most important insights learned by students during acquiring the Civil Defence course. To find out the attitude of the pedagogical specialties students towards the Civil Defence course, a questionnaire of the first-year students was carried out after the acquisition of the course. The responses of full-time and part-time students were compared. The results of the questionnaire showed that the majority of the surveyed students have understood the importance of the Civil Defence course and they consider that this course is necessary for all study programs. After completing the course, most students have understood the most important topics of the Civil Defence course. The majority of surveyed students consider that topics related to national defence should be included in the Civil Defence course. As the most interesting topics students have found first aid, disasters and their classification and disaster management. Students believe that Civil Defence knowledge is needed for being aware of how to deal with emergencies, if necessary, to be able to provide first aid and for better understanding of the functioning of the civil defence system in Latvia. Students see an opportunity to combine the acquiring of Civil Defence course with the mastering of another study course.